Assessment of gated community and guarded neighbourhood from public perspective - Abdullah, Muhammad Faris; Mohd Daniar, Nurul Ain; Mohamed Osman, Mariana; Bachok, Syahriah (American Scientific Publishers, 2017)
In recent years, Gated and Guarded community schemes (GACOS) have been gaining increased popularity among house buyers. This phenomenon can be attributed to the demand for heightened safety and security among house buyers. Scholars agreed that GACOS have managed to improve safety and security of residents but criticised the impacts of GACOS on community relationship in urban areas. GACOS are said to create segregation between the haves and the have-nots and are symbol of wealth and status. This study investigates the perception of non-GACOS residents towards GACOS to see their acceptance of the schemes. It is found that non-residents are favourable to the GACOS concept, mainly due to safety and security reason. They also do not associate GACOS to exclusivity and status.